2016
DOI: 10.1159/000448059
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy in the Elderly Patient: Age-Adapted Risk Assessment

Abstract: Background: Older patients are increasingly faced with pancreatic surgery because of shifting demographics. The differential effects of aging on surgical outcomes remain vague, while the elderly patient is often neglected in clinical trials. Methods: Medical records of 370 patients who underwent pancreaticoduodenectomy were analyzed. Patients were then subdivided into 3 groups according to age and comorbidities. Results: Overall mortality was 5% and did not significantly differ between age-matched groups. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…As a result, the rate of surgical resection in elderly patients has increased (1). However, elderly patients often have multiple comorbidities with functional impairment, tissue vulnerability, and are generally considered to have a high risk of postoperative complications after highly invasive surgery, such as pancreatectomy, which might cause protracted decline in their activities of daily living (20)(21)(22)(23). Therefore, for elderly patients, safer surgical techniques or management to minimize complications following pancreatic resection, namely, pancreatic fistula, are required so that patients suffer no loss of independence or productivity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the rate of surgical resection in elderly patients has increased (1). However, elderly patients often have multiple comorbidities with functional impairment, tissue vulnerability, and are generally considered to have a high risk of postoperative complications after highly invasive surgery, such as pancreatectomy, which might cause protracted decline in their activities of daily living (20)(21)(22)(23). Therefore, for elderly patients, safer surgical techniques or management to minimize complications following pancreatic resection, namely, pancreatic fistula, are required so that patients suffer no loss of independence or productivity.…”
Section: Discussionmentioning
confidence: 99%
“…39,43,44 However, longer operation times and higher incidences of organ injury. [45][46][47] are of particular concern when considering LPD surgery for elderly patients. 48 One retrospective analysis of robot-assisted PDs concluded that the procedure can be performed safely in elderly patients with mortality, morbidity, and outcomes comparable to those in younger patients.…”
Section: ) Pancreaticoduodenectomy (Pd)mentioning
confidence: 99%
“…However, those selected for laparoscopic PD are predominantly otherwise healthy patients under the age of 75, with good performance status; thus, the extrapolation of results from such trials to daily practice necessitates careful consideration. Longer operation times and higher incidences of organ injury 9,10,11,12 , are of particular concern when considering LPD surgery for elderly patients 13 . One retrospective analysis of Robot-assisted PDs concluded that the procedure can be performed safely in elderly patients with mortality, morbidity, and outcomes comparable to those in younger patients 14 .…”
Section: Introductionmentioning
confidence: 99%